The Applications of Medical Tattooing in the Head and Neck Region - Hou, Zhe; Lee, Patrick K. (Facial Plastic Surgery, 2019)
Medical tattooing has been used in various circumstances. In this review, the authors focus on the utilization of medical tattooing in the head and neck region as a minimally invasive alternative to corrective surgeries. It is mostly used to camouflage noticeable surgical scars on scalp, face, and perioral areas. Its use has also been described in cases of concealing depigmentation or hypopigmentation, hair loss, postirradiation telangiectasia, and congenital vascular malformation. These procedures are well-tolerated and safe. Its effects are long-lasting and satisfactory, leading to improvement in self-esteem and increased quality of life in treated patients. The limitations of medical tattooing in such uses include high technical requirement, color fading and alteration, unpredictable outcomes in scarred tissue, and potential cutaneous reactions. It also carries a risk of infection, albeit very low due to standardized sterilization process in a medical setting. The authors conclude that medical tattooing in the head and neck region may serve as an excellent option for patients who seek for cosmetic improvement in their deformities and/or discoloration but would prefer to avoid surgery.
Keywords: dermatography; surgical scars; camouflage; medical tattooing